2007
DOI: 10.1007/s00586-007-0414-y
|View full text |Cite
|
Sign up to set email alerts
|

Are animal models useful for studying human disc disorders/degeneration?

Abstract: Intervertebral disc (IVD) degeneration is an often investigated pathophysiological condition because of its implication in causing low back pain. As human material for such studies is difficult to obtain because of ethical and government regulatory restriction, animal tissue, organs and in vivo models have often been used for this purpose. However, there are many differences in cell population, tissue composition, disc and spine anatomy, development, physiology and mechanical properties, between animal species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
669
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 614 publications
(685 citation statements)
references
References 154 publications
14
669
1
1
Order By: Relevance
“…The cow is considered to have a similar IVD as humans, with retention of few notochordal cells [16,23]. However, the exact relationship between cow age and NC content is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…The cow is considered to have a similar IVD as humans, with retention of few notochordal cells [16,23]. However, the exact relationship between cow age and NC content is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that these fibrils penetrate beyond the cement line and merge with those present in both the CEP and VEP. This work has been performed in sheep, where it is known that, as in other animal species, the growth plate for the vertebrae is located within the centre of the vertebral body [1]; in contrast to in humans where it is an integral part of the CEP. The effect of growth plate location and the degeneration process on collagen integration at the CEP-VEP interface thus remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility and safety assessment of percutaneous insertable/removable interspinous spacer A young porcine model (3-month-old, female, LWD) was selected due to its relative similarity in size in spinous processes to adult human beings [1], especially in the upper level of the lumbar spine such as L1-2 and 2-3. A total of 14 animals were used for this current study.…”
Section: Methodsmentioning
confidence: 99%